Review Of Intellectual Property Law On Micro, Small, And Medium Enterprise Products Of Selar Fish Crackers In Warnasari Village, Cilegon City - Sulasno, Sulasno; Lestari, Deviana; Abdillah, Farid (Journal Of Social Science (JoSS), 2024)
Micro, Small, and Medium Enterprises (MSMEs) activities in Cilegon City are one of the growing business sectors to support the national economy.. For business actors starting a business, they need to think about the concept of business and intellectual property protection. In the business world, Intellectual Property can be one of the important elements because it can give the owner an advantage over the results of his invention. This study aims to determine the concept and product innovation of Micro, Small, and Medium Enterprises (MSMEs), Selar Fish Crackers in Warnasari Village, Citangkil District, Cilegon City, and to determine the legal protection of intellectual property for Micro, Small, and Medium Enterprises (MSME products), Selar Fish Crackers in Warnasari Village, Citangkil District, Cilegon City. This research uses qualitative methods and empirical juridical approaches. Where the research is conducted by looking at the law as a norm or das sollen and as a socio-cultural reality or das sein obtained directly from the research location. The data analysis technique uses descriptive analytical techniques. The results showed that the concept and innovation of MSMEs is the first step taken to develop the Akbar Jaya Fish Crackers business and protect intellectual property in its products, one of which is by registering the brand to the Directorate General of Intellectual Property to obtain legal certainty.